The Internationalization Program of State Universities: Student’s Perspective - Aulia Luqman Aziz; Beleven Khrismawan; Dini Kurnia Irmawati (Universitas Brawijaya, 2021)
Internationalization has been promoted in many universities worldwide to improve education management, students, and alumni within the dynamic era of globalization. Universitas Brawijaya (UB), as one of the leading universities in Indonesia, is also implementing the internationalization strategy to realize the mission and vision as a World Class Entrepreneurial University. One of the efforts in the internationalization strategy is the “3 in One” Program that involves visiting professors from foreign countries, practitioner-lecturers, and internal lecturers in the implementation of education, research, and community service. This study aimed to evaluate the implementation of the “3 in One” Program in UB by emphasizing students’ perspectives as service users of university services or UB services. The study was qualitative using a survey method. The population was all students in study programs that have joined the “3 in One” Program. Samples were chosen using stratified random sampling. Data were collected using a questionnaire adapted from Student Evaluation of Educational Quality (SEEQ) and semi-structured interviews. Findings showed that 212 respondents (87.6%) knew that the “3 in One” Program involved a visiting professor, a practitioner-lecture, and a lecture from UB. It is expected that UB could improve its socialization of the concept of the “3 in One” program within the study programs or UB’s lecturers and to students. The study programs are expected to have better preparations to minimize language barriers in the “3 in One” Program. The study programs and the university are also encouraged to conduct regular evaluations on the “3 in One” Program.